Treatment of pemphigus vulgaris: part 2 – emerging therapies. (3rd October 2019) - Yanovsky, Rebecca L.; McLeod, Michael; Ahmed, A.Razzaque
ABSTRACT: Introduction : Corticosteroids and immunosuppressive agents have been the mainstay for the treatment of pemphigus vulgaris (PV). While they have benefited patients, they have been associated with the risks of prolonged immune suppression and a high incidence of significant and catastrophic side effects. Relapses are common. Novel agents promising targeted therapies, that may provide better outcomes, are being studied. Areas covered : Recently rituximab with corticosteroids has been recommended as the first-line treatment for PV. A number of known and new therapeutic agents currently investigated are BAFF, P13K, BTK inhibitors along with the use of IVIg and CAR-T therapy. The possible role of these therapeutic targets in the pathophysiology appears to be the rationale for the treatment of this potentially fatal disease. Expert opinion : While there is significant enthusiasm for these therapies, certain concerns and consequences are being under-discussed. None of the current clinical trials in progress are specific for PV, except possibly CAR-T therapy. The major issue(s) that are unclear is whether these therapies would be successful in providing long-term clinical remissions. Will these therapies require additional agents to be effective? Will the benefits be limited in duration? The answers to many questions will determine their final place in the algorithm for the treatment of PV.